Serological survey of equine herpesvirus infection in Minas Gerais state - Lara, Maria do Carmo Custódio de Souza Hunold; Torelli, Camila Souza; Cunha, Elenice Maria Sequetin; Villalobos, Eliana Monteforte Cassaro; Cunha, Mariana Sequetin; Bello, Ana Cristina P. P.; Cunha, Arildo P.; Reis, Jenner K. P.; Leite, Rômulo Cerqueira; Mori, Enio (Brazilian Journal of Veterinary Research and Animal Science, 2010)
Equine herpesvirus type 1 (EHV-1) and 4 (EHV-4) are major pathogens affecting horses, and cause respiratory disease, abortion, perinatal mortality and neurological disease, bringing economical losses. This infection has been reported worldwide, but there are only a few studies in Brazil. The present study was undertaken in order to evaluate the occurrence and distribution of equine herpesviruses (EHV) infection in equids from ten regions of Minas Gerais State: Almenara, Bambuí, Curvelo, Governador Valadares, Montes Claros, Oliveira, São Gonçalo do Sapucaí, Teófilo Otoni, Unaí and Viçosa. To detect antibodies against EHV virus neutralization test in microplates was used. We found 17.6% (145/826) positive animals for EHV. 18.7% (140/749) positive horses, 6.8% (5/73) positive mules and none positive (0/4) donkeys. All ten regions studied showed animals reagents to EHV. The results suggest that EHV is widespread in equids of Minas Gerais State. It was observed a higher occurrence of antibodies against EHV in adult animals, indicating the potential of these animals as source of infection for foals.